Determination of the concentration of Ce, La, Sm and Eu in a phosphogypsum stack, in Imbituba city, Santa Catarina, Brazil - Borges, Renata Coura; Marques, Letícia Mombrini; Mahler, Cláudio Fernando; Bernedo, Alfredo Victor Bellido (Eclética Química, 2018)
Phosphate fertilizer industry produces phosphoric acid from phosphate rocks, and as a byproduct, it produces phosphogypsum, also known as agricultural gypsum. This material was stock an open-air stacks near the producing units. In order to determine levels of rare-earth elements in phosphogypsum stacks, located in Imbituba, Brazil. Samples of 1000 grams of phosphogypsum were collected in nine different points in stack 1. The concentration of rare-earth elements was determined through neutron activation analysis and results indicate significant values of rare earth elements in the phosphogypsum from Imbituba, when compared to the values of the Earth’s crust.